LIFE AND THOUGHT IN THE GREEK AND ROMAN WORLD - Cary, M. (Max), 1881-1958. Link ([S.l.])
1 online resource
Keywords: Life and Thought in the Greek and Roman World (1961) aims to provide a brief but comprehensive outline sketch of Greek and Roman civilization. It describes the geographic, political and social background of that civilization, and sets forth its main achievements in the fields of language and literature, scholarship and education, science and philosophy, art and religion. The authors have endeavoured throughout to present Greek and Roman civilization as an organic whole.